PENGARUH PERUBAHAN BEBAN GENERATOR SINKRON TERHADAP SISTEM EKSITASI STUDI KASUS PT. PLN INDONESIA POWER UPK PLTA MANINJAU: PENGARUH PERUBAHAN BEBAN GENERATOR SINKRON TERHADAP SISTEM EKSITASI STUDI KASUS PT. PLN INDONESIA POWER UPK PLTA MANINJAU - M.Chaisar Al Furqon, Furqon (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2024)
Generators play an important role in providing electrical energy in power systems. Changing loads on generators in an interconnected system can cause voltage instability. The generator voltage can be regulated through excitation current, which is a DC electrical supply that amplifies the field in the generator to produce electrical energy with an output voltage that depends on the excitation current. The purpose of this study is to analyze the effect of synchronous generator load changes on the excitation system on the generator and the effect of excitation current on the generator voltage of unit 2 of Maninjau Hydroelectric Power Plant. The type of excitation system at Maninjau Hydropower Plant is an excitation system with PMG, the output voltage of unit 2 generator of Maninjau Hydropower Plant is 10 kV. The method used in this research is by looking at the data read on the generator load data and the excitation current read on the DCS parameters. Furthermore, from the data obtained, the generator voltage value is in the range of 10.3 kV - 10.6 kV. This shows that the AVR component works well in reading and giving commands in regulating the generator output voltage. From the data obtained, the value of load changes in the generator affects the value of the injected excitation current. The lowest load is at 10.4 MW with an injected excitation current value of 8 A and the generator voltage is at 10.6 kV, while the largest load is at a value of 16.5 MW with a higher excitation current value.